Peningkatan Pengetahuan Tentang Tokoh Sejarah Melalui Aplikasi Tiktok Pada Peserta Didik - Ervi Rahmadani (JURNAL NALAR PENDIDIKAN, 2022)
This study aims to determine the increase in knowledge of historical figures through the introduction of biographies in class VIII students of SMPN Satap 7 Maiwa Enrekang Regency by using the Tiktok application. This type of research is classroom action research using a quantitative approach. The sample in this study amounted to 18 students who were in class VIII.The research was conducted using a test instrument in the form of multiple choice as many as 20 items given to students at the pretest and posttest, the results of which were used to determine the increase in students' knowledge about historical figures. The results obtained that the average pretest score of 18 students was 51% who were in the poor category (K) while the posttest average value was 76.6% which was in the good category (B). So descriptively there was an increase of 25.6% of students' knowledge about historical figures. The results of the statistical test also show that the t value is -7,405 < 0.000 or the significance value is greater than the t value, so that there is a significant effect on the introduction of biographies using the Tiktok application as a media.